Upaya Pemberdayaan Masyarakat dalam Pencegahan dan Pengendalian Hipertensi di Desa Sungai Cuka - Nita Pujianti; Agus Dwi Rachmannur; Dewi Firani; Elma Meilani; Pramesty Reggia Kusumawardhaeny (Pusat Riset dan Inovasi Nasional, 2023)
The prevalence of hypertension in South Kalimantan is 44.1%. In Tanah Bumbu Regency, hypertension is among the top 10 diseases. Coastal areas, like Desa Sungai Cuka, have a high risk of hypertension due to residents' habit of processing seafood with salting as a preservation method. To address this, the community service team implemented the CERDIK program, which involved providing education through posters, counseling, and various tools such as leaflets, digital tensimeters, blood test cards, powerpoints, and pre-post test questionnaires. The program, conducted in August 2022, resulted in a significant change in people's behavior, including regular exercise and reduced salt consumption, to prevent hypertension. These positive outcomes indicate the success of the program delivered by the community service team in Desa Sungai Cuka.